Physical descriptions of the Beechey Island headboards. (10th August 2017) - Hansen, Todd
ABSTRACT: In August 2016, the author was able to personally examine the five Beechey Island Franklin era gravesite headboards, in the collections of the Government of Nunavut and currently preserved at the Prince of Wales Northern Heritage Center in Yellowknife, NT, Canada. Except for the inscriptions, there appears to be relatively little physical description actually published in the literature, and this article summarises those observations and some conclusions drawn from this examination.